2009
DOI: 10.1128/jvi.01346-09
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Chemokines in Rabies Virus Infection: Overexpression May Not Always Be Beneficial

Abstract: It was found previously that induction of innate immunity, particularly chemokines, is an important mechanism of rabies virus (RABV) attenuation. To evaluate the effect of overexpression of chemokines on RABV infection, chemokines macrophage inflammatory protein 1␣ (MIP-1␣), RANTES, and IP-10 were individually cloned into the genome of attenuated RABV strain HEP-Flury. These recombinant RABVs were characterized in vitro for growth properties and expression of chemokines. It was found that all the recombinant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 52 publications
5
83
0
Order By: Relevance
“…This observation, together with previous studies investigating the role of IFN in rabies (28,33,36), questions the efficiency of IFN in controlling RABV infection in the NS. In the same vein, since several studies have pointed out that infiltrating T cells recruited into the brain by chemokines have a direct antiviral effect on RABV infection (14,19,59), it was expected that mice exhibiting reduced T cell infiltration, as LGP2 TG mice do, would be less able to control RABV spread in the NS than WT mice. In striking contrast, LGP2 TG mice, not WT mice, eliminated RABV infection from the brain at day 11 p.i.…”
Section: Discussionmentioning
confidence: 99%
“…This observation, together with previous studies investigating the role of IFN in rabies (28,33,36), questions the efficiency of IFN in controlling RABV infection in the NS. In the same vein, since several studies have pointed out that infiltrating T cells recruited into the brain by chemokines have a direct antiviral effect on RABV infection (14,19,59), it was expected that mice exhibiting reduced T cell infiltration, as LGP2 TG mice do, would be less able to control RABV spread in the NS than WT mice. In striking contrast, LGP2 TG mice, not WT mice, eliminated RABV infection from the brain at day 11 p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses were titrated via direct fluorescent antibody assays in BSR cells as described previously (11). Briefly, BSR cells seeded in 96-well plates were inoculated with serial 10-fold dilutions of the virus and incubated at 37°C for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…CVS-B2c is a RABV that was attenuated in the laboratory by passaging the challenge virus standard (CVS-24) in baby hamster kidney (BHK21) cells (31). The recombinant virus HEP-CXCL10 (rHEP-CXCL10) was constructed in our laboratory previously (7). A fluorescein isothiocyanate (FITC)-conjugated anti-RABV nucleoprotein antibody was obtained from Fujirebio (Malvern, PA).…”
Section: Methodsmentioning
confidence: 99%
“…In the mouse model, inflammation is mild after infection with wild-type (wt) RABV (6). However, extensive inflammation, apoptosis, and expression of innate immune genes have been found in the CNSs of mice infected with laboratory-attenuated RABV (7)(8)(9)(10)(11)(12). Recently, it has been found that blood-brain barrier (BBB) permeability is enhanced in mice infected with laboratory-attenuated, but not wt, RABV (10,13).…”
mentioning
confidence: 99%